Incidence, treatment and outcome of central nervous system relapse in adult acute lymphoblastic leukaemia patients treated front‐line with paediatric‐inspired regimens: A retrospective multicentre Campus ALL study. (6th November 2022) - Dargenio, Michelina; Bonifacio, Massimiliano; Chiaretti, Sabina; Vitale, Antonella; Fracchiolla, Nicola Stefano; Papayannidis, Cristina; Giglio, Fabio; Salutari, Prassede; Audisio, Ernesta; Scappini, Barbara; Zappasodi, Patrizia; Defina, Marzia; et al.
Summary: Within the Campus ALL network we analyzed the incidence, characteristics, treatment and outcome of a central nervous system (CNS) relapse in 1035 consecutive adult acute lymphoblastic leukemia (ALL) patients treated frontline with pediatric‐inspired protocols between 2009 and 2020. Seventy‐one patients (6.8%) experienced a CNS recurrence, more frequently in T‐ (28/278; 10%) than in B‐ALL (43/757; 5.7%) ( p  = 0.017). An early CNS relapse—< 12 months from diagnosis—was observed in 41 patients. In multivariate analysis, risk factors for early CNS relapse included T‐cell phenotype ( p  = <0.001), hyperleucocytosis >100 × 10 9 /L ( p <0.001) and male gender ( p  = 0.015). Treatment was heterogeneous, including chemotherapy, radiotherapy, intrathecal therapy and novel agents. A complete remission (CR) was obtained in 39 patients (55%) with no differences among strategies. After CR, 26 patients underwent an allogenic transplant, with a significant overall survival benefit compared to non‐transplanted patients ( p  = 0.012). After a median observation of 8 months from CNS relapse, 23 patients (32%) were alive. In multivariate analysis, the time to CNS relapse was the strongest predictor of a lower 2‐year post‐relapse survival ( p <0.001). In conclusion, in adult ALL the outcome after a CNS relapse remains very poor. Effective CNS prophylaxis remains the best approach and allogenic transplant should be pursued when possible.